علاقة خصائص شخصية المربي لإكساب مهارة التقليد غير اللفظي للأطفال ذوي الاحتياجات الخاصة - بهدنة, كريمة (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة بالعربية هدفت الدراسة الحالية إلى التعرف على وجود علاقة خصائص شخصية المربي لإكساب مهارة التقليد غير اللفظي للأطفال ذوي الاحتياجات الخاصة، وتكمن أهمية الدراسة في أنها استهدفت مجموعة أطفال من ذوي الاحتياجات الخاصة مختلفي الإعاقة (صعوبات التعلم، إعاقة سمعية، فرط الحركة وتشتت الانتباه، إعاقة ذهنية بسيطة، متلازمة داون، التوحد)، كذلك شريحة من مربي ومربيات ذوي الاحتياجات الخاصة داخل المركز النفسي البيداغوجي للمعاقين ذهنيا والأقسام الخاصة التابعة لها. وللإجابة على تساؤلات الدراسة تمت صياغة الفرضيات التالية: 1. الفرضية العامة: توجد علاقة بين خصائص شخصية المربي لإكسابهم مهارة التقليد غير اللفظي لأطفال ذوي الاحتياجات الخاصة. 2. الفرضيات الجزئية: • توجد علاقة بين خاصية الإنسانية لإكساب مهارة التقليد غير اللفظي لأطفال ذوي الاحتياجات الخاصة. • توجد علاقة بين خاصية الحماس لإكساب مهارة التقليد غير اللفظي للأطفال ذوي الاحتياجات الخاصة. • توجد علاقة بين خاصية الطيبة لإكساب مهارة التقليد غير اللفظي للأطفال ذوي الاحتياجات الخاصة. • توجد علاقة بين خاصية المرونة لإكساب مهارة التقليد غير اللفظي للأطفال ذوي الاحتياجات الخاصة. وتحقيقا لأهداف الدراسة تم الاعتماد على المنهج الوصفي الارتباطي، كذلك تطبيق مقياسين الأول تم على عينة من المربين والمربيات قوامهم (40) "استبيان الخصائص الشخصية للمربي اعداد/الباحثة"، والمقياس الثاني على الأطفال ذوي الاحتياجات الخاصة قوامهم (40) "بطاقة ملاحظة لمهارة التقليد غير اللفظي اعداد/الباحثة" وذلك بالمركز النفسي البيداغوجي للمعاقين ذهنيا -تقرت- والأقسام الخاصة التابعة لها. وبعد جمع البيانات تم تفريغها ومعالجتها احصائيا باستخدام البرنامج الاحصائي spss للتحقق من الفرضيات، وقد أظهرت نتائج الدراسة ما يلي:  تحقق الفرضية العامة بوجود علاقة بين خصائص شخصية المربي لإكسابهم مهارة التقليد غير اللفظي لأطفال ذوي الاحتياجات الخاصة.  تحقق الفرضيات الجزئية حسب كل خاصية (الإنسانية-الحماس-الطيبة-المرونة) بوجود علاقة بين كل خاصية واكساب مهارة التقليد غير اللفظي للأطفال ذوي الاحتياجات الخاصة. Abstract of the study in English: The current study aimed to identify the existence of a relationship between the characteristics of the educator is personality to acquire the skill of non-verbal Imitation for children with special needs. Down autism, as well as a segment of educators with special needs with in the psychological center pedagogy for the mentally handicapped and its special sections.  In order to answer the study questions, the following hypotheses were formulated: • The general premise: There is a relationship between the characteristics of the educator is personality to provide them with the skill of non- verbal imitation of children with special needs. • the partial hypotheses: 1) There is a relationship between the characteristic of humanity to acquire the skill of non-verbal imitation for children with special. 2) There is a relationship between the characteristic of enthusiasm to acquire the skill of non-verbal imitation of children with special needs. 3) There is relationship between the characteristic of kindness to acquire the skill of non-verbal resilience for children with special needs. 4) There is relationship between the characteristic of flexibility to acquire the non-verbal imitation skill of children with special needs.  In order to achieve the objectives of the study, the descriptive, correlative approach was relied upon, as well as the application of two measures. The skill of non-verbal imitation was prepared by the researcher at the psychological and pedagogical center for the Mentally Handicapped-dugout- and its affiliated departments. And after collecting the data, it was emptied and processed statistically using the SPSS statistical program to verify the hypotheses. The results of the study showed the following: o The general hypothesis is that there are differences between educators with positive earn them personality characteristics and educators with negative characteristics in the skill of non-verbal imitation for people with special needs, which lies in the high positive characteristics of personality among educators. o Partial hypotheses are verified according to each characteristic (humanity-enthusiasm- kindness-flexibility) and there are differences between educators with high degrees and those with low degrees in acquiring the skill of non-verbal imitation for people with special needs, which is represented in the high degrees of all personal characteristics.
دراسة وصفية بالمركز النفسي البيداغوجي للمعاقين ذهنيا -تقرت-
مذكرة ماستر في علوم التربية تخصص تربية خاصة
Keywords: مربي الأطفال، Baby-sitter, babysitter; مهارة التقليد، Compétence d'imitation، Imitation skill